2004
DOI: 10.1093/qjmed/hci007
|View full text |Cite
|
Sign up to set email alerts
|

Trends in adult renal replacement therapy in the UK: 1982-2002

Abstract: Despite significant expansion in RRT services for adults in the UK over the last 20 years, there is evidence of unmet need, and need is expected to rise, due to demographic changes and trends in type 2 diabetes. Continuing growth in the already substantial investment in RRT will be needed, unless efforts to prevent the occurrence of ERF are successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…T he epidemiology of ESRD has been studied extensively using large databases such as the United States Renal Data System and similar registries in Canada, Europe, Australia, and New Zealand (1)(2)(3)(4). In contrast, the epidemiology of acute renal failure (ARF) in hospitalized patients is less well understood, having been derived largely from single-center retrospective studies that used detailed review of medical records (5)(6)(7).…”
mentioning
confidence: 99%
“…T he epidemiology of ESRD has been studied extensively using large databases such as the United States Renal Data System and similar registries in Canada, Europe, Australia, and New Zealand (1)(2)(3)(4). In contrast, the epidemiology of acute renal failure (ARF) in hospitalized patients is less well understood, having been derived largely from single-center retrospective studies that used detailed review of medical records (5)(6)(7).…”
mentioning
confidence: 99%
“…Similar demographic trends have been observed in the United States and the United Kingdom [3,4]. Cross-sectional studies have shown older haemodialysis patients are generally less active and more physically impaired than younger patients [3,5,6]. In addition older dialysis patients suffer from a high degree of disability and functional dependence [6][7][8][9].…”
Section: Introductionmentioning
confidence: 79%
“…Fifty-five percent of all new dialysis patients are 65 years of age and older, and almost 25% are 75 years and older [2]. Similar demographic trends have been observed in the United States and the United Kingdom [3,4]. Cross-sectional studies have shown older haemodialysis patients are generally less active and more physically impaired than younger patients [3,5,6].…”
Section: Introductionmentioning
confidence: 95%
“…Consequently with an increasing DM global prevalence and an aging population, DM has become the leading single cause of ESRD in many developed and developing countries [19][20][21][22][23][24]. Moreover, it is now proven that even a mild reduction in kidney function is accompanied by an increased cardiovascular (CV) risk [25,26].…”
Section: Risk In Diabetic Kidney Diseasementioning
confidence: 99%